2013
DOI: 10.1111/add.12394
|View full text |Cite
|
Sign up to set email alerts
|

Family transitions and changes in drinking from adolescence through mid‐life

Abstract: Aims To examine how changes in social roles, particularly in the family, predict rises and falls in alcohol consumption from ages 16 to 50. Design Longitudinal data from the National Child Development Study. Setting The birth cohort includes 99% of British infants born in one week in 1958. Participants After initial assessment of 17,415 infants, the cohort was interviewed at ages 7, 11, 16, 23, 33, 42, 46, and 50. This study uses the six adolescent through adult waves (n = 7,212 women, 7,377 men). Meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
52
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 44 publications
(90 reference statements)
1
52
0
Order By: Relevance
“…Evidence suggests that maturing out of heavy drinking is, at least in part, a result of the acquisition of adult roles and responsibilities such as marriage and/or parenthood, end of formal education and start of employment, change in living arrangements, and financial independence (Bachman et al, 2002; Eitle, Taylor, & Eitle, 2010; Fleming, White, & Catalano, 2010; Kretsch & Harden, 2014; Staff, Greene, Maggs, & Schoon, 2014). These relations may be a result of both role selection and role socialization.…”
mentioning
confidence: 99%
“…Evidence suggests that maturing out of heavy drinking is, at least in part, a result of the acquisition of adult roles and responsibilities such as marriage and/or parenthood, end of formal education and start of employment, change in living arrangements, and financial independence (Bachman et al, 2002; Eitle, Taylor, & Eitle, 2010; Fleming, White, & Catalano, 2010; Kretsch & Harden, 2014; Staff, Greene, Maggs, & Schoon, 2014). These relations may be a result of both role selection and role socialization.…”
mentioning
confidence: 99%
“…Pregnancy and child birth mark an important transition in a woman’s life characterized by psychosical, economic and logistical changes (Rutter, 1996), and thus may facilitate a reduction in alcohol consumption through changing norms, expectations and added responsibilities associated with being a parent (Fergusson, Boden, & John Horwood, 2012; Staff, Greene, Maggs, & Schoon, 2014). On the other hand, increased responsibilities and expectations associated with caring for a young child may also lead to stressful challenges in a woman’s life, which may reverse the initial protective effect of parenthood on drinking (Wolfe, 2009).…”
mentioning
confidence: 99%
“…(3 times a month or more) was more common among 18/19-year-olds (40%) than among 25/26-year-olds (24%). The development from 2008 to 2015 corresponds to the phenomenon "maturing out", described in international research where young people's drinking has been shown to peak in their early 20s, after which it declined when they take on new responsibilities, in terms of employment and family relations [30,31,34,35]. Contrary to findings in previous research, maturing out among our respondents was not significantly related to their occupational status (employment, unemployment, studies), nor was it associated with background characteristics such as parents' education or divorce.…”
Section: Discussionmentioning
confidence: 99%
“…Young adults in a relationship 2015: We control for whether the respondents were in a relationship in 2005, 2008 or 2015, as previous research also suggests that steady, romantic relationships may influence people's drinking habits [29][30][31]. Thus, the young adults were asked if they currently had a girlfriend/boyfriend or (in later waves) a spouse.…”
Section: Parents' Education 2005mentioning
confidence: 99%